2005
DOI: 10.1385/jmn:26:2-3:209
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A<SUB>2A</SUB> and Dopamine D<SUB>2</SUB> Heteromeric Receptor Complexes and Their Function

Abstract: The existence of A2A-D2 heteromeric complexes is based on coimmunoprecipitation studies and on fluorescence resonance energy transfer and bioluminescence resonance energy transfer analyses. It has now become possible to show that A2A and D2 receptors also coimmunoprecipitate in striatal tissue, giving evidence for the existence of A2A-D2 heteromeric receptor complexes also in rat striatal tissue. The analysis gives evidence that these heteromers are constitutive, as they are observed in the absence of A2A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(132 citation statements)
references
References 51 publications
4
125
0
3
Order By: Relevance
“…Constant FRET 50 values for each receptor in homo-and heterodimeric complexes could indicate no difference in the functional state adopted by each receptor. By analogy to BRET parameters, however, we can also assume that if energy transfer reaches saturation and the curve is hyperbolic, FRET 50 would allow estimation of the apparent affinity between the partners involved (25,26,29). This concurs with the similar affinities reported for X1 and X2 homo-and heterodimers (12).…”
Section: Discussionsupporting
confidence: 69%
“…Constant FRET 50 values for each receptor in homo-and heterodimeric complexes could indicate no difference in the functional state adopted by each receptor. By analogy to BRET parameters, however, we can also assume that if energy transfer reaches saturation and the curve is hyperbolic, FRET 50 would allow estimation of the apparent affinity between the partners involved (25,26,29). This concurs with the similar affinities reported for X1 and X2 homo-and heterodimers (12).…”
Section: Discussionsupporting
confidence: 69%
“…In the corpus striatum and mesolimbic areas, where the two receptors mostly co-localise [20], it has been demonstrated that they are structurally associated to form functional heterodimers in which the adenosine and dopamine receptors mutually antagonise their respective responses [21][22][23][24][25]. On the basis of these results, A 2A AR agonists have been suggested as possible drugs, in association with antipsychotics, for the treatment of psychotic symptoms in schizophrenia and bipolar disorders [26,27].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Adenosine A 1 and A 2A receptors form functional heteromeric complexes with dopamine D 1 and D 2 receptors (DRD 1/2 , Fuxe et al, 2005) and there is evidence that these receptors interact at multiple levels to control cell function. First, the receptors physically interact and binding of adenosine to A 2A reduces affinity of DRD 2 for dopamine (Torvinen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%